A twisted love story - Downing, Samantha (Berkley, 2023)
"From the bestselling author of My Lovely Wife comes a reckless, delicious thriller about a young couple that gives a whole new meaning to the dangers of modern dating. Ivy and Wes know they are meant to be. There's no other way to describe the feelings they have for each other except to blame it on fate and being soul mates. What starts with a first date, then a first kiss, turns into an intensely passionate love affair that neither of them will ever be able to walk away from--no matter how hard they try and, believe me, they've tried. But they're back together again and swear this time will be different. No more games, no more drama, and certainly no more crimes. Orange jumpsuits aren't a good look for either of them. They know their friends, family, and the police aren't rooting for their happily-ever-after. But they'll prove them all wrong. If you're meant to be, nothing will stand in your way"--